Pengaruh Fungisida Berbahan Aktif Tunggal dan Campuran Metiltiofanat dan Karbendazim Terhadap Pertumbuhan Jamur Colletotrichum scovillei Secara In Vitro - TESSALONIKA G SIANIPAR; KHAMDAN KHALIMI; I DEWA PUTU SINGARSA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2023)
The Effect of Concentration of Single Active Ingredients and Mixture of Methylthiofanate and Carbendazim on the Growth Of Mushrooms Colletotrichum scovillei In Vitro Anthracnose is still the main disease in chili plants, anthracnose in chili peppers can be caused by some of the fungal species Colletotrichum. According to a report obtained from a field survey in 2018 found that Colletotrichum scovillei fungus is a species that infects large chili plants in Bali. An effort to control anthracnose is to use fungicides with active ingredients methylthiofanate and carbendazim. This study aims to determine the appropriate concentration of fungicides with the active ingredients of methylthiofanate, carbendazim and a mixture of methylthiofanate and carbendazim to inhibit the growth of the fungus C. scovillei in vitro. The fungicide inhibition test was carried out using the Poisoned Food Technique. The results showed that the active ingredient fungicide methylthiofanate, carbendazim, a mixture of methylthiofanate and carbendazim at a concentration of 1.5 ml/l effectively inhibited the growth of the fungus C. scovillei in vitro. The results of this study provide information that the tested fungicides are effective in inhibiting the growth of the fungus C. scovillei which causes anthracnose on chili peppers in Bali.